1963
DOI: 10.1063/1.1729317
|View full text |Cite
|
Sign up to set email alerts
|

Defect Structure and Density Decrease in Neutron-Irradiated Quartz

Abstract: Lattice defects in quartz induced by fast neutron irradiation were studied by combined methods of x-ray diffraction and transmission electron microscopy. The developed defect structure is characterized by clusters of interstitials enriched in ruptured silicon atoms. The size and density of the defect clusters increase with increasing dose until mutual interaction occurs, resulting in the formation of a stable, hexagonal-like structure resistant to prolonged annealing at 500°C. In thin crystals the size and vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

1964
1964
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 5 publications
2
14
0
Order By: Relevance
“…As shown in the introduction, the integrity of a CBS is normally evaluated by determining the limit of fast neutron fluence and/or gamma-ray dose, which depend on the authorities or countries. Previous studies have suggested that the concrete strength deteriorates above a fast neutron (>0.1 MeV) fluence of 10 19 n/cm 2 under the temperature condition of light water reactors (Hilsdorf et al 1978;Field et al 2015), while the minimum neutron energy that affects α-quartz is 0.01 MeV (Primak 1958;Weissmann and Nakajima 1963;Bykov et al 1981). Further scientific research is needed to confirm this criterion.…”
Section: Integrity Evaluationmentioning
confidence: 97%
“…As shown in the introduction, the integrity of a CBS is normally evaluated by determining the limit of fast neutron fluence and/or gamma-ray dose, which depend on the authorities or countries. Previous studies have suggested that the concrete strength deteriorates above a fast neutron (>0.1 MeV) fluence of 10 19 n/cm 2 under the temperature condition of light water reactors (Hilsdorf et al 1978;Field et al 2015), while the minimum neutron energy that affects α-quartz is 0.01 MeV (Primak 1958;Weissmann and Nakajima 1963;Bykov et al 1981). Further scientific research is needed to confirm this criterion.…”
Section: Integrity Evaluationmentioning
confidence: 97%
“…Numerous groups have studied quartz as an expanding rock mineral (Wittels and Sherrill 1954;Primak et al 1955;Primak 1958;Weissmann and Nakajima 1963;Lell et al 1968;Bykov et al 1981;Inui et al 1990;Eby et al 1992;Bonnet et al 1994;Douillard and Duraud 1996;Bolse 1999;Ewing et al 2000). Yet, the rate of metamictization and the final expansion strain of other rock-forming minerals are also important topics for research.…”
Section: Concretementioning
confidence: 99%
“…(1) can also be interpreted in a slightly modified form, which corresponds, mathematically speaking, to the form adopted by several researchers, e.g., (Larive 1997;Saouma and Perotti 2006), to model the expansion of concrete subjected to alkali-silica reaction (ASR) as a function of time. Substitution of time by the fluence Φ leads to: (Wittels 1957;Primak 1958;Weissmann and Nakajima 1963 As noted by Bykov et al, "the very strong temperature effect in the range of 30 °C to 100 °C and the reduction of this effect at a higher temperature indicates a nonuniformity of distribution of the defects with respect to the energy of activation, in particular, to a reduction of the fraction of defects with an increased energy of activation." Hence, instead of trying to interpret the data with the calibration of an apparent energy activation, temperature effects are analyzed directly on how Zubov's parameters are affected.…”
Section: A Model For the Effects Of Temperature And Neutron Irradiatimentioning
confidence: 93%